Conceptual modelling of the flow of frail elderly through acute-care hospitals: An evidence-based management approach. Issue 10 (8th October 2018) - Bruzzi, Silvia; Landa, Paolo; Tànfani, Elena; Testi, Angela
Abstract : Purpose: The ageing of the world's population is causing an increase in the number of frail patients admitted to hospitals. In the absence of appropriate management and organisation, these patients risk an excessive length of stay and poor outcomes. To deal with this problem, the purpose of this paper is to propose a conceptual model to facilitate the pathway of frail elderly patients across acute care hospitals, focussed on avoiding improper wait times and treatment during the process. Design/methodology/approach: The conceptual model is developed to enrich the standard flowchart of a clinical pathway in the hospital. The modified flowchart encompasses new organisational units and activities carried out by new dedicated professional roles. The proposed variant aims to provide a correct assessment of frailty at the entrance, a better management of the patient's stay during different clinical stages and an early discharge, sending the patient home or to other facilities, avoiding a delayed discharge. The model is completed by a set of indicators aimed at measuring performance improvements and creating a strong database of evidence on the managing of frail elderly's pathways, providing proper information that can validate the model when applied in current practice. Findings: The paper proposes a design of the clinical path of frail patients in acute care hospitals, combining elements that, according to an evidence-based management approach, have proved to be effective in terms of outcomes, costs and organisational issues. The authors can, therefore, expect an improvement in the treatment of frail patients in hospital, avoiding their functional decline and worsening frailty conditions, as often happens in current practice following the standard path of other patients. Research limitations/implications: The framework proposed is a conceptual model to manage frail elderly patients in acute care wards. The research approach lacks application to real data and proof of effectiveness. Further work will be devoted to implementing a simulation model for a specific case study and verifying the impact of the conceptual model in real care settings. Practical implications: The paper includes suggestions for re-engineering the management of frail elderly patients in hospitals, when a reduction of lengths of stay and the improvement of clinical outcomes is required. Originality/value: This paper fulfils an identified need to study and provide solutions for the management of frail elderly patients in acute care hospitals, and generally to produce value in a patient-centred model.